If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x = 4(x + -2.25) Reorder the terms: 3x = 4(-2.25 + x) 3x = (-2.25 * 4 + x * 4) 3x = (-9 + 4x) Solving 3x = -9 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 3x + -4x = -9 + 4x + -4x Combine like terms: 3x + -4x = -1x -1x = -9 + 4x + -4x Combine like terms: 4x + -4x = 0 -1x = -9 + 0 -1x = -9 Divide each side by '-1'. x = 9 Simplifying x = 9
| C-55=110 | | 6y-5x+7x-y= | | -6x+2(4x+18)=16 | | Ln(13)+ln(4)= | | H(t)=-5t^2+10t | | -4(2b-5)=34 | | z=20-11.6 | | C-3=58 | | x+8.4=20 | | 1y=42-4y | | 7p/2=14 | | b-5=35 | | -5(x-1)+3=-2(X+3)-8 | | z=20-(20+-1y) | | g(x)=3x^2+2x+18 | | 96=-32t^2+128t | | 5a-9/5-2a=-4/7 | | 2x-x^2=-35 | | z=42-4(14) | | 2x-x^2=35 | | 6a+7b+5=16 | | h=54-1/3t | | -.01x^2+.6x+5.8=0 | | 4p^3=4p(p+2) | | -y/6=-40 | | 821/1,000 | | z=20-(20+y) | | 4s=2f/(a-b) | | x2/2-5/6=12 | | 2/3x-11=14 | | 11*3-12/4 | | N*5=165 |